THE SOIL ALGAE OF CIBODAS FOREST RESERVE - Johnson, Anne (REINWARDTIA, 1974)
Three species of green algae and one blue-green alga were recorded from eight samples of soil found associated with bryophytes in the Cibodas Forest Reserve. Chemical analysis of the soil showed severe leaching of soluable mineral substances associated with a low pH. The low light intensity under forest conditions and the low pH may account for the limited algal flora.